Phase transition kinetics and microstructures of A508-3 steel under continuous cooling process. Issue 1 (31st December 2022) - Liu, Yong; Qu, Nan; Ren, Jianwei; Zhang, Yan; Zhu, Jingchuan
ABSTRACT: The phase transition kinetics of A508-3 steel during continuous cooling were studied by high temperature transition instrument which was based on thermodilatometry in this paper. The microstructures during continuous heating and cooling were also observed. The transition points were determined to be austenite formation temperatures, A c1  = 757°C, A c3  = 823°C, and martensitic transformation start and final temperatures, Ms  = 382°C, Mf  = 222°C at the cooling rate of 5°C/s. The curves of Austenite transition fraction and time during continuous heating show a typical S shape. And the Austenite will show a maximum transition rate value at the middle temperature. The volume fraction of new phases translated from Austenite as functions of time and temperature during the cooling process can be obtained using the lever law. The pearlite transitions can occur in high-temperature regions at cooling rate smaller than 0.1°C/s. And Bainite can be gotten at a lower temperature region. The S-type curves can be used to describe the relationships between the transition volume fraction and time. Increasing the cooling rate enhances the volume fraction of Martensite at the cooling rate ≥5°C/s. And only Martensite transition can be observed at the cooling rate >10°C/s. And Ms and Mf increase with increasing cooling rate. The Martensite transition kinetics equation with changing temperature was obtained. Finally, the continuous cooling transformation curves of A508-3 steel were constructed, which can be used to predict the microstructure and design the heat treatment technologies.